Pulmonary fibrosis complicated by lung cancer: bibliometric analysis from 2004 to 2024 - research status, trends and future directions - Li, Boyang; Wu, Fan; Ma, Xinlai; Yuan, Weishan; Li, Jiaqing; Zhang, Wei; Liu, Xue (Frontiers in Immunology, 2025)
ObjectiveAlthough research on the association between pulmonary fibrosis and lung cancer is of great significance, to date, no bibliometric analysis has been conducted on the comorbidity of these two diseases. This study aims to explore the current status and cutting - edge trends in this field through bibliometric analysis, and to establish new directions for future research.MethodsUsing the Web of Science Core Collection database, statistical calculations, graphic, and data visualization tools such as CiteSpace, VOSviewer, and Biblimatrix - biblioshiny were adopted.ResultsA total of 2,234 original Articles and Reviews on pulmonary fibrosis complicated by lung cancer published between 2004 and 2024 were identified. A slow growth trend in publications related to pulmonary fibrosis complicated by lung cancer was observed. The United States, Japan, and China were the countries with the greatest contributions. Professor Michael Kreuter from Marienhaus Clinic, Mainz, Germany, and the University of Michigan published the most articles. Through cluster analysis of co - cited literature, five main clusters were identified. Keyword analysis predicted that “nintedanib”, “pirfenidone”, “immunotherapy”, etc. might become hot topics in the field of the comorbidity of pulmonary fibrosis and lung cancer.ConclusionThis bibliometric analysis shows that the literature related to the comorbidity of pulmonary fibrosis and lung cancer is on a continuous upward trend. The research hotspots and trends identified in this study provide a reference for in - depth research in this field, aiming to promote the development of research on the comorbidity of pulmonary fibrosis and lung cancer.